Some features of pre-processing of RTK network LitPOS (Lithuania) data applying Bernese software - Baniulis, Rimvydas; Galinauskas, Karolis; Paršeliūnas, Eimuntas; Petniūnas, Marius (International Conference “Environmental Engineering”, 2017)
LitPOS (Lithuanian Positioning System), the network of permanent reference GNSS stations, became operational in July 2007. It provides data both for real-time and post-processing applications. LitPOS stations cover the whole territory of Lithuania. Total number of LitPOS GNSS stations during 2007–2014 period was 25 (since 2015 – 30 stations). Also LitPOS network includes 3 ASG UPOS (Poland) and 6 LATPOS (Latvia) stations. LitPOS network data re-processing was done using Bernese (BSW5.2 update 2016 01 08) software. Software was slightly improved by editing scripts and writing procedures for RINEX files preparation, for downloading other necessary data, and for getting two processing solutions from single BPE (Bernese Process Engine) process (total network and sub-network without Polish and Latvian stations).